PENGARUH SUPERVISI KEPALA SEKOLAH DAN MOTIVASI MENGAJAR GURU TERHADAP KEDISIPLINAN GURU PKN SMK SWASTA KOTA PEKANBARU - Zulfa Adli; Hasnah Faizah Ar, Ridwan Manda Putra (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This study examines the effect of principal supervision and teaching motivation on the discipline of Civic Education teachers at private vocational schools in Pekanbaru. The research employed a correlational design with a quantitative approach and involved 69 Civic Education teachers from all private vocational schools in Pekanbaru. Data were analyzed using simple and multiple linear regression. The results indicated that principal supervision significantly influenced teachers’ discipline, contributing 46.2%, while teaching motivation also had a significant effect, contributing 42.3%. Simultaneously, principal supervision and teaching motivation jointly affected teachers’ discipline, contributing 53.2%.